SPATIAL DISCOURSE AND THE REPRESENTATION OF THE COURT: RELATIONS BETWEEN THE CHILDREN ACT AND BLEAK HOUSE - Escoza, Cassia [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2017)
This article proposes a comparative analysis between the works Bleak House (1853) by Charles Dickens and The Children Act (2014) by Ian McEwan, using figurative semiotic studies. Observing the similarities and differences of the narrative space contained within the two novels, enables the understanding of the stylistic and formal aspects used by these authors as well as the historical and cultural context in which they arose. The analysis reveals the close connection between the two narratives, more specifically, the relationship between literature and legal processes of English society in the mid-nineteenth century and early twenty-first century.
Keywords: Charles Dickens; Ian McEwan; Figurative semiotics; Law and Literature